A methods engineering study on Kagitingan Printing Press, Inc. - Cuaresma, Katherine (College of Engineering, 1996)
The system under study is the Kagitingan printing press, Inc. (KPPI, the official printer of the news daily, the Manila Standard, Savvy magazine and other publications. The study is divided into two major parts, Methods Study and Systems and Procedures Analysis. In methods study, the main goal/objective is to increase the labor productivity of the said company. Interviews and actual observations were done to gather the necessary data. The study used the Stream Analysis to find out what the core problem of the company is. From here, development of alternatives and their evaluation was done to know what area contributes greatly to the core problem and what alternative should be implemented in order to effect the most improvement. The whole of the methods study was focused on creating a new plant layout and facilities design for the company. Proposals were made, and if implemented, would yield beneficial results such as decreasing the total distance traveled, improving work flow, thus increasing labor productivity. In the systems and procedures analysis, there were two parts, namely organizational analysis wherein no problems were found and forms analysis with a few minor revisions. The forms used by the company were all in standard form .The problem lies with the distribution of some forms to their respective destinations. Proposals on forms color coding were presented for implementation. It is also recommended that manuals be provided to the workers. The manuals should contain everything from company's background up to how to do specific jobs. This would lead to better understanding between management and workers as well as providing necessary information to the workers.